Medical and dietary properties of malt extracts - Mukoid, Roman (My University, 2013)
Extract polisol made from malt, have a therapeutic dietary properties, thanks to a set of biologically active substances of malt. Given the valuable chemical composition of malt cereals (oats, corn, barley) developed dietary supplements based on them and studied their nutritional value.
Keywords: malt; oats; grain; солод; зерно; вівсяний; овсяный; кафедра біотехнології продуктів бродіння і виноробства